Green synthesis of silver nanoparticles from polygonum minus extract and its antimicrobial properties / Nadzirah Abu Samah... [et al.] - Abu Samah, Nadzirah; Mahamudin, Massuri; Muhamad, Salina; Ibrahim, Abdul Latif (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Nanotechnology is the study and advanced/modern application of small object that can be practised across various scientific fields, such as physics, chemistry, biology, material science, engineering, etc. It has been widely applied in the 21 st century, and it also paved the way to the green approach in technology in the form of green nanotechnology. The field of nanotechnology enables silver nanoparticles (AgNPs) to be widely used as novel therapeutic agents in the semblance of antibacterial, antifungal, antiviral, anti-inflammatory, and anti-cancerous agents. In this study, plant extract of Polygonum minus (known as kesum) was used for the synthesis of AgNPs from silver nitrate (AgNO 3 ) solution. The green synthesis, which is an alternative way to produce silver nanoparticles, was proposed because it is cost-effective and environmentally friendly. The colourless reaction mixture was observed to slowly change from yellowish-green to reddish-brown, indicating the reduction of silver ion after several minutes of reaction. The AgNPs were characterised by Ultraviolet-visible (UV-Vis) spectrophotometer, Field-emission Scanning Electron Microscope (FE-SEM), and Energy-Dispersive X-Ray Spectroscopy (EDX). The results obtained from the UV-Vis spectrophotometer showed a sharp peak absorbance at 440 nm, which indicated the reduction of Ag + to metallic Ag. Meanwhile, the size of AgNPs observed via FE-SEM was in the range of 15-25 nm. Accordingly, based on the EDX analysis, 82.6% of AgNPs were determined to show strong peaks for silver (Ag). Three bacteria, i.e. Staphylococcus aureus (ATCC 43300), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 15442) were chosen to be tested in this study. The morphological changes of bacterial cells treated with AgNPs were observed by FE-SEM, showing that the AgNPs have excellent antimicrobial properties against microorganisms. Thus, the ability of AgNPs to release Ag ions is a critical factor in its antimicrobial activity.